2019
DOI: 10.1111/are.14296
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the Amazonian planktivorous catfish Hypophthalmus marginatus (Siluriformes, Pimelodidae)

Abstract: We evaluated the annual process of oocyte and ovarian development of the planktivorous Amazonian catfish, the mapará (Hypophthalmus marginatus), aiming to support captive reproduction for domestication. A total of 149 females were captured from the Tocantins River at the Tucuruí Dam (3°49'55"S, 49°39'9"W) in 13 sampling events. For each individual, we evaluated ovary histology and plasma steroid concentrations. Two annual reproductive cycles, with similar characteristics, including a long period of rest, a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In this context, one of the bottlenecks for the consolidation of its production in captivity, for aquaculture and preservation purposes, is the attainment of viable embryos through hormonal induction. When kept in captivity, ovarian and testicular maturation takes place, reaching more advanced stages of maturation between November and February (rainy season in Brazil) and, as well as the majority of tropical reophilic fish, hormonal stimulation is required for spawning (Borella et al, 2019;Hainfellner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, one of the bottlenecks for the consolidation of its production in captivity, for aquaculture and preservation purposes, is the attainment of viable embryos through hormonal induction. When kept in captivity, ovarian and testicular maturation takes place, reaching more advanced stages of maturation between November and February (rainy season in Brazil) and, as well as the majority of tropical reophilic fish, hormonal stimulation is required for spawning (Borella et al, 2019;Hainfellner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the curimbatá was among the migratory species most affected by the fact that the closure of the river prevents its upward reproductive migration and limits its recolonization in the downstream from upstream, the same reason cannot be attributed to the reduction in the abundance of mapará, as it carried out its entire migratory cycle in the downstream area, so it is very likely that there was also a decrease in plankton production due to a degradation of the aquatic environment (Mérona et al, 2010). Still concerning maparás, a fish that we studied due to its high potential for integrated aquaculture purposes for being planktivorous, in the same area reported by Mérona et al (2010), we published a study in 2019 where maparás were observed upstream and downstream the dam, but in the immediate downstream portion very close to the dam, spawned individuals were not found, and only mature females were observed (absence of spawning) (Hainfellner et al, 2019). We also observed that some females found downstream from the dam, however at a slightly greater distance, indeed had postovulatory follicles, indicating that they had spawned in those areas, but not in the dam area (Hainfellner et al, 2019).…”
Section: Section 3: Illustrative Examples On the Effect Of Dams On Fi...mentioning
confidence: 65%
“…Still concerning maparás, a fish that we studied due to its high potential for integrated aquaculture purposes for being planktivorous, in the same area reported by Mérona et al (2010), we published a study in 2019 where maparás were observed upstream and downstream the dam, but in the immediate downstream portion very close to the dam, spawned individuals were not found, and only mature females were observed (absence of spawning) (Hainfellner et al, 2019). We also observed that some females found downstream from the dam, however at a slightly greater distance, indeed had postovulatory follicles, indicating that they had spawned in those areas, but not in the dam area (Hainfellner et al, 2019).…”
Section: Section 3: Illustrative Examples On the Effect Of Dams On Fi...mentioning
confidence: 65%
See 1 more Smart Citation
“…The VSI peak (Figure 5) occurs twice at full moon. The reduction in VSI during spawning was also studied by Hainfellner et al (2019) in Amazonian planktivorous catfish, Hypophthalmus marginatus. This species continues to feed and increases the VSI to a maximum (3%) when entering the spawning season, the VSI will decrease.…”
Section: Discussionmentioning
confidence: 99%